Balancing Innovation and Integrity in the Pacific: Exploring the Dual Impact of AI on Tertiary Education in Fiji - Davendra Sharma (International Journal of Social Sciences, Language and Linguistics, 2025)
The rapid integration of artificial intelligence (AI) into tertiary education is reshaping how students learn, interact, and prepare for the future. This paper critically examines the dual impact of AI on higher education, highlighting both its potential to enhance learning and the ethical challenges it presents. On the positive side, AI enables personalized learning pathways, expands access to resources, automates routine tasks, and equips students with future-ready skills. Conversely, risks include over-reliance on technology, threats to academic integrity, unequal access, and concerns about privacy and the dehumanization of learning. Drawing on recent studies, the article argues that the transformative promise of AI in higher education can only be realized if institutions adopt balanced strategies that integrate innovation with ethical safeguards. The paper concludes by proposing policy and pedagogical frameworks that promote responsible AI use, ensuring that technological advancement complements, rather than compromises, academic integrity and holistic student development.